An examination of concentration and mental toughness in professional basketball players - Dereceli, C. (Journal of Education and Training Studies, 2019)
This study was carried out to investigate the concentration and mental toughness of professional basketball players. A total of 290 professional basketball players aged 16-26 years who played in the Turkish Basketball First and Second Leagues participated in the study. The "Sport Mental Toughness Questionnaire (SMTQ-14)" developed by Sheard et al. (2009) was used to determine mental toughness levels of the basketball players participating in the study, and the "Letter Cancellation Task" scale developed by Kumar and Telles (2009) was used to determine their concentration levels. Data were analyzed by using the Kolmogorov-Smirnov test, an independent samples t-test, and one-way analyses of variance (ANOVA).